Pengungkapan Corporate Social Responsibility dari Perspektif Board Governance Gender Diversity - Khanza, Mudhi’ah; Putri, Amellia; Kariima, Fitami Hasanatul; Putri, Elda Maihardina; Zaitul, Zaitul (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This research aims to determine the effect of gender diversity (on the board of commissioners, board of directors, and audit committee), company size, and company age on corporate social responsibility (CSR) disclosure. The object of this research is the company operating in the agricultural products sector, consisting of 22 companies listed on the Indonesia Stock Exchange. Secondary data is collected using observation techniques in annual report data and sustainability reports. This research has three variables: dependent variable (corporate social responsibility) and independent variables (gender diversity in the board of commissioners, gender diversity in the board of directors, gender diversity in the audit committee, company size, and company age). The research showed that only one hypothesis is accepted (H4): company size significantly negatively influences CSR disclosure. In addition, Gender diversity of the board of commissioners, board of directors, audit committee, and company age does not influence CSR disclosure.